Fortes chaleurs et circulation atmosphérique associée autour de la Méditerranée orientale : cas du littoral tunisien et syro-libanais - Myriam Traboulsi; Habib Ben Boubaker (Territoire en Mouvement, 2012)
The eastern Mediterranean is is characterized by temperature contrasts between the east and west shores. In particular, comparative analysis of high temperatures between the Tunisian east coast and the Levantine one shows a higher exposure of the latter in terms of frequency and intensity. The regional atmospheric circulation and local factors, especially those of relief, justify these contrasts.